Innokentiy Safianov – a politician, philanthropist and a regional ethnographer - Kuzhuget, Aylana K. (The New Research of Tuva, 2011)
Article describes unrenowned aspects of activities and interests of I.G. Safianov, a co-founder of Tuvan statehood. Politician reveals as a patron of science and a regional ethnographer.
Keywords: I. G. Safyanov; history of Tuva; local history; philanthropist; photos; I. S. Kon; Tuvan people's Republic